2021
DOI: 10.1002/elsc.202000093
|View full text |Cite
|
Sign up to set email alerts
|

One‐step selective affinity purification and immobilization of His‐tagged enzyme by recyclable magnetic nanoparticles

Abstract: The NiFe2O4 magnetic nanoparticles (NF‐MNPs) were prepared for one‐step selective affinity purification and immobilization of His‐tagged recombinant glucose dehydrogenase (GluDH). The prepared nanoparticles were characterized by a Fourier‐transform infrared spectrophotometer and microscopy. The immobilization and purification of His‐tagged GluDH on NF‐MNPs were investigated. The optimal immobilization conditions were obtained that mixed cell lysis and carriers in a ratio of 0.13 in pH 8.0 Tris‐HCl buffer at 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 49 publications
(55 reference statements)
0
16
0
Order By: Relevance
“…Nonetheless, the immobilization enabled repeatable measurements in a flow injection system for over three days of extensive use at 60 tests/day [79]. Other methods enabling controlled quantitative enzyme immobilization, such as exploiting the nickel-histidine affinity in the case of His-tagged enzymes [84], immobilization on nanomaterials with high loading capacities [85], enzyme nanoflowers [86], CLEAs, or other recent strategies [83] could lead to better performance of immobilized F-ALDH.…”
Section: Kinetics Of the Recombinant F-aldhmentioning
confidence: 99%
“…Nonetheless, the immobilization enabled repeatable measurements in a flow injection system for over three days of extensive use at 60 tests/day [79]. Other methods enabling controlled quantitative enzyme immobilization, such as exploiting the nickel-histidine affinity in the case of His-tagged enzymes [84], immobilization on nanomaterials with high loading capacities [85], enzyme nanoflowers [86], CLEAs, or other recent strategies [83] could lead to better performance of immobilized F-ALDH.…”
Section: Kinetics Of the Recombinant F-aldhmentioning
confidence: 99%
“…Lower V max values after enzyme immobilization were similarly reported before [33,81]. In another study, Zhou et al reported about a 6.7-fold decrease in the V max value after the immobilization of a His-tagged recombinant glucose dehydrogenase (GluDH) on NiFe 2 O 4 magnetic nanoparticles [74].…”
Section: Comparison Of Free and Immobilized Gdo Kinetic Parametersmentioning
confidence: 77%
“…One-step immobilization and purification methods have been applied before for a Histagged transaminase [41], a histidine-tagged green fluorescent protein [72], an extracellular His-tagged Thermomyces lanuginosus lipase [73], and even for the co-immobilization of two components of hydroxylase monooxygenase that were employed to construct a bienzymatic catalytic system [46]. Moreover, Zhou et al studied the selective purification and immobilization of a His-tagged recombinant glucose dehydrogenase onto NiFe 2 O 4 magnetic nanoparticles in a one-step procedure [74]. The abovementioned methodology allowed for the selective purification of the recombinant GDO through immobilization on the nanocarriers.…”
Section: Immobilization Of Recombinant Gentisate 12-dioxygenasementioning
confidence: 99%
“…Adsorption and ionic binding are quite simple and low-cost methods, but non-specific. Affinity binding is highly selective, enables one pot purification and immobilization and allows oriented enzyme immobilization, yet it is costly [44,[65][66][67][68][69]. Chemical attachment to the carrier involves covalent binding through amide, carbamate, ether or thio-ether bonds established between groups of suitable residues on the enzyme surface and on the carrier (Figure 1d 1 ) [36,67].…”
Section: Classification Of Immobilization Methods and Their Key Featuresmentioning
confidence: 99%